Multicompartment Nanoparticles by Crystallization‐Driven Self‐Assembly of Star Polymers: Combining High Stability and Loading Capacity. Issue 4 (23rd November 2022) - Huo, Haohui; Zou, Jing; Yang, Shu‐Gui; Zhang, Jiaqi; Liu, Jie; Liu, Yutong; Hao, Yanyun; Chen, Hongfei; Li, Hui; Huang, Chaobo; Ungar, Goran; Liu, Feng; et al.
Abstract: Herein novel multicompartment nanoparticles (MCNs) that combine high stability and cargo loading capacity are developed. The MCNs are fabricated by crystallization‐driven self‐assembly (CDSA) of a tailor‐made 21 arm star polymer, poly(L‐lactide)[poly( tert ‐butyl acrylate)‐ block ‐poly(ethylene glycol)]20 [PLLA(P t BA‐ b ‐PEG)20 ]. Platelet‐like or spherical MCNs containing a crystalline PLLA core and hydrophobic P t BA subdomains are formed and stabilized by PEG. Hydrophobic cargos, such as Nile Red and chemotherapeutic drug doxorubicin, can be successfully encapsulated into the collapsed P t BA subdomains with loading capacity two orders of magnitude higher than traditional CDSA nanoparticles. Depolarized fluorescence measurements of the Nile Red loaded MCNs suggest that the free volume of the hydrophobic chains in the nanoparticles may be the key for regulating their drug loading capacity. In vitro study of the MCNs suggests excellent cytocompatibility of the blank nanoparticles as well as a dose‐dependent cellular uptake and cytotoxicity of the drug‐loaded MCNs. Abstract : Multicompartment nanoparticles (MCNs) with crystalline core and amorphous hydrophobic subdomains are fabricated showing both high stability and cargo loading capacity. Depolarized fluorescence measurements suggest that the weaker geometric confinement of the subdomains by core crystals may be the key for high drug loading capacity.